2019
DOI: 10.5194/acp-2019-38
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Remote biomass burning dominates southern West African air pollution during the monsoon

Abstract: <p><strong>Abstract.</strong> Vast quantities of agricultural land in southern and central Africa are burnt between June and September each year, which releases large concentrations of aerosols into the atmosphere. The resulting smoke plumes are carried west over the Atlantic Ocean at altitudes between 2 and 4 km. As only limited observational data in West Africa have existed until now, whether this pollution has an impact at lower altitudes has remained … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 28 publications
(41 reference statements)
0
20
1
Order By: Relevance
“…Namely, the onset of West African monsoon flow is related to the surface pressure contrast between the SHL, which develops due to the intense surface heating during boreal summer (Lavaysse et al, 2009), and relatively cool waters of the eastern tropical Atlantic. Typically, the monsoon onset occurs around the end of June (Janicot et al, 2008;Sultan and Janicot, 2003), while during 2016 its onset occurred on 22 June (Knippertz et al, 2017). Therefore, the differences in the NLLJ for cloudy and clear nights found in previous work could be related to the analysis of a larger number of nights from the pre-monsoon or late monsoon period compared to our analysis.…”
Section: Discussioncontrasting
confidence: 50%
“…Namely, the onset of West African monsoon flow is related to the surface pressure contrast between the SHL, which develops due to the intense surface heating during boreal summer (Lavaysse et al, 2009), and relatively cool waters of the eastern tropical Atlantic. Typically, the monsoon onset occurs around the end of June (Janicot et al, 2008;Sultan and Janicot, 2003), while during 2016 its onset occurred on 22 June (Knippertz et al, 2017). Therefore, the differences in the NLLJ for cloudy and clear nights found in previous work could be related to the analysis of a larger number of nights from the pre-monsoon or late monsoon period compared to our analysis.…”
Section: Discussioncontrasting
confidence: 50%
“…These dry layers most likely originated from a central and southern African dry air mass, which is typically filled with biomass burning aerosol, and is transported to the west over the eastern tropical Atlantic in the layer between 2-4 km a.g.l. (Haslett et al, 2019). Haslett et al (2019) have found that a considerable proportion of the biomass 25 burning aerosol (smoke) is entrained into the marine boundary layer and advected northwards with the southerly trade winds towards the Coast of Guinea.…”
Section: Discussionmentioning
confidence: 99%
“…(Haslett et al, 2019). Haslett et al (2019) have found that a considerable proportion of the biomass 25 burning aerosol (smoke) is entrained into the marine boundary layer and advected northwards with the southerly trade winds towards the Coast of Guinea. This conclusion is supported by the evidence of aged aerosol particles which were measured by a research aircraft (Flamant et al, 2018;Haslett et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations